2007
DOI: 10.3390/12030607
|View full text |Cite
|
Sign up to set email alerts
|

Methyl Jasmonate and Salicylic Acid Induced Oxidative Stress and Accumulation of Phenolics in Panax ginseng Bioreactor Root Suspension Cultures

Abstract: Abstract:To investigate the enzyme variations responsible for the synthesis of phenolics, 40 day-old adventitious roots of Panax ginseng were treated with 200 µM methyl jasmonate (MJ) or salicylic acid (SA) in a 5 L bioreactor suspension culture (working volume 4 L). Both treatments caused an increase in the carbonyl and hydrogen peroxide (H 2 O 2 ) contents, although the levels were lower in SA treated roots. Total phenolic, flavonoid, ascorbic acid, non-protein thiol (NPSH) and cysteine contents and 1,1-diph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
81
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(99 citation statements)
references
References 51 publications
15
81
1
2
Order By: Relevance
“…3a, b and c). The fact that Me-J influences the secondary metabolism of plants is already established and reported (Ali et al 2007). Generally, phenolics and flavonoids are anti-oxidative in nature and are produced in the phenyl-propanoid pathway (Heller and Forkmann 1988;Lister et al 1996).…”
Section: Elicitation Of Adventitious Roots In Liquid Mediummentioning
confidence: 91%
“…3a, b and c). The fact that Me-J influences the secondary metabolism of plants is already established and reported (Ali et al 2007). Generally, phenolics and flavonoids are anti-oxidative in nature and are produced in the phenyl-propanoid pathway (Heller and Forkmann 1988;Lister et al 1996).…”
Section: Elicitation Of Adventitious Roots In Liquid Mediummentioning
confidence: 91%
“…Moreover, the exogenous treatment of plants with SA broadly displayed a transcript profile of paralogous ReCHS genes that was found to be in consonance with the increasing content of both flavonoids and anthraquinones. Additionally, several studies have shown that MeJ and SA are prospective candidates for the elicitation process leading to the transcriptional alteration of various genes that ultimately affect secondary metabolite biosynthesis (Ali et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…9J; Supplemental Table S2). SA treatments also have resulted in significant increases in the flavonoid content in root suspension cultures of Panax ginseng (Ali et al, 2007).…”
Section: Effects Of Abiotic Elicitors On Rechs Expression Vis-à-vis Fmentioning
confidence: 99%
“…Ces composés, notamment les isoflavones sont également capables d'améliorer les troubles vasomoteurs en diminuant l'intensité et la fréquence des bouffées de chaleur (Amiot et al, 2012), de réduire la résorption osseuse et de stimuler la formation osseuse (Lecerf, 2007). Les polyphénols, de par leurs activités anti-inflammatoires et analgésiques (Babar Ali et al, 2007), sont capables de soulager les femmes des douleurs musculaires et articulaires qu'elles pourraient ressentir.…”
Section: Régime Alimentaire Des Femmesunclassified